DAMPAK KEKERASAN DALAM RUMAH TANGGA TERHADAP KARAKTER ANAK - Edy Sofyan; Ernandia Pandikar (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2017)
ABSTRACT The family is the first environment in a child's life, a place where children learn and express themselves as social beings. The family provides the basis for the formation of behavior, character, morals and education of the child. Triggers of violence against children that occur among others are first, the emergence of domestic violence, the occurrence of violence involving both the father, mother and other relatives cause inevitable violence occurs also against children. Children are often targeted by parents' anger. Second, the occurrence of family dysfunction, namely the role of parents do not work as they should. Third, the economic factor, namely violence arises because of economic factors. The character of the child will be disturbed by the occurrence of wrong treatment that often escape the attention, whereas ordinary events are very often related, in the inability and ineffective parents in dealing with children. The problem formulation in this study is how big the role of parents according to legislation and norms prevailing in society, the factors causing the occurrence of violence in the household, and how big the character of children who experience violence in the household. The research method used a quantitative descriptive approach. As for the results from the average research scores the study mostly answered